The Yörüks and Antiquity in the West Antalya - Tiryaki, Salih Gökhan (Journal of History Culture and Art Research, 2022)
The history of Antalyan archaeology is more comprehensive than biographies of leading excavations or sensational discoveries. Thanks to the recent reviews on early studies, we understand better now how ruling political, ideological and ethical values deeply affected the archaeological interpretations of the region's past. This phenomenon has particular importance for the Yörüks who were held responsible for the destruction of the Greco-Roman antiquity in Lycia and Milyas referring to their Asiatic descent, Mohammedan faiths and pastoral way of life. These assumptions which built constantly renewing “synthetic” conflict zones between the Yörüks and the long-term history of Antalya are in fact not based on any provable arguments but on personal experiences or worldviews. In that sense, the present study tries to understand the multiphased relations between the Yoruk population and the West Antalyan antiquity within the frame of archaeological evidences and indigenous archive documents such as Tax Registries of Teke Sanjak. As a consequence, it has been argued here that excluding the Yörüks as "others" from the cultural landscape of the region will also prevent us to understand the long-term history of Antalya.